Penerapan Terapi Aktivitas Kelompok Stimulasi Persepsi untuk Mengontrol Halusinasi Auditori - Lulu Luckysa Nirwana; Endah Sari Purbaningsih; Erida Fadila (CV. ALIM'SPUBLISHING, 2026)
Schizophrenia is a chronic mental disorder in which approximately 90% of sufferers experience hallucinations, dominated by auditory hallucinations at 70%. Pharmacological approaches alone are considered insufficient because they often leave residual symptoms. Therefore, non-pharmacological interventions such as Group Activity Therapy (TAK) Perception Stimulation are needed to improve patients’ self-control abilities. This case study aims to evaluate the application of TAK Perception Stimulation in controlling auditory hallucinations in schizophrenia patients in Lily 13 Room, Prof. Dr. Soerojo Hospital, Magelang. This study employed a descriptive case study using the nursing process approac. The study subjects consisted of 5 schizophrenia patients with active auditory hallucination problems. Data were collected through interviews, observations, mental status examinations, and medical record documentation studies. The TAK Perception Stimulation Intervention was conducted for 4 consecutive days on January 6–10, 2026. After the 4-day intervention, all patients experienced an increase in adaptive ability in controlling auditory hallucinations with based on the AHRS observational checklist maximum score of 5. All subjects succeeded in independently recognizing the content and time of hallucinations, practicing reprimand techniques, participating in regularly scheduled activities, actively conversing with others, and complying with medication, accompanied by a decrease in the frequency of hallucinations. Patients also appeared to be calmer and more cooperative.